WOMEN’S EMPOWERMENT AND GENDER REPRESENTATION IN RUN THE WORLD (GIRLS) BY BEYONCÉ: A FEMINIST LITERARY CRITICISM STUDY - Reny Krisdayanti Sianipar; Aulia Ahmad Panjaitan; Amelia Marsha Fadilah; T. Thyrhaya Zein; Aisyah Michelle (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study examines women’s empowerment and gender representation in Beyoncé’s Run the World (Girls) through the perspective of feminist literary criticism proposed by Tyson (2015). The study aims to investigate how the song constructs and communicates women’s empowerment through five dimensions: leadership and authority, confidence and superiority, dual roles of women, women’s solidarity, and economic independence. This research employs a qualitative design using documentation and library research techniques. The primary data consist of the song lyrics of Run the World (Girls), while secondary data are obtained from scholarly books, journal articles, and previous studies related to feminism, gender representation, and popular music. The data were analyzed using the procedures proposed by Miles, Huberman, and Saldaña (2014) and Creswell and Poth (2018). The findings reveal that the song portrays women as capable leaders who possess authority and influence, confident individuals who challenge gender stereotypes, resilient figures who balance domestic and professional responsibilities, members of a supportive collective community, and economically independent actors who contribute to social and economic development. Through these representations, the song challenges patriarchal assumptions and promotes feminist values of agency, equality, and empowerment. The study concludes that Run the World (Girls) functions as a feminist cultural text that advocates women’s empowerment and contributes to contemporary discussions on gender equality. Keywords: women’s empowerment, gender representation, feminist literary criticism, Beyoncé, Run the World (Girls)